Worsted, Weave, and Web: The Cultural Struggles of the Fictional Knitting-Woman - Kathy REES (E-REA)
In comparison with needlework, knitting has always been regarded as a rather humble domestic art, and consequently less critical attention has been paid to its representation in fictional literature. In this article, Mrs Brown, the knitting protagonist of A. S. Byatt’s short story, “Art Work” (1994), provides a lens through which themes of inequality and injustice in social, political, racial, and sexual contexts are explored in relation to the “knitting-woman” as she appears in novels written between 1840 and 1940. The act of knitting is based on the repetition of two stitches, plain and purl, creating a fabric by moving forwards and backwards, and on the shaping of a garment by increasing or decreasing stitches. This article replicates those two movements, shifting between the present and the past, and tracing the periodical fluctuations in female fortunes as they advanced and regressed. Many fictional knitting-women were culturally marginalised figures, whose struggles with different forms of oppression were articulated through knitting-related actions and language. Few of these women realised their aspirations, and it was not until the late twentieth century, when knitting became recognised as an art form rather than a simple utilitarian craft, that fictional characters like Mrs Brown could achieve status and independence.